Co-combustion Characteristics and Kinetics Behavior of Torrefied Sugarcane Bagasse and Lignite - Ukrit Samaksaman; Kanit Manatura (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The co-combustion characteristics and kinetics of torrefied sugarcane bagasse (TB), lignite (L), and their blended samples were experimentally investigated using thermogravimetric analysis (TGA) and derivative thermogravimetry (DTG)based on the Coats-Redfern method for kinetic estimation.Their physicochemical properties were also investigated.Raw bagasse was thermally treated in a laboratory-scale torrefactor at 275 °C with a torrefaction time of 60 min under an inert nitrogen environment.Then, the torrefied bagasse was blended with Thai lignite as a co-fuel at ratios of 50:50 (TB50L50), 70;30(TB70L30), and 90:10 (TB90L10), respectively. Torrefaction improved the fuel properties and heating value of the raw bagasse as well as reducing the O/C and H/C ratios.In addition, the blending of torrefied bagasse with lignite improved the combustion behavior.The TGA and DTG results indicated that the ignition and burnout temperatures stepped downwards with different increasing ratios of torrefied bagasse.The co-combustion behavior at the maximum burning rate showed that the burnout temperatures of TB50L50, TB70L30, and TB90L10 were 532, 529, and 528 °C, respectively, indicating a slight decrease with an increasing torrefied bagasse blending ratio.These results were sufficient to provide comprehensive guidelines in terms of the design and operation of the combustion system for adding torrefied bagasse into the co-firing process.